IDEOLOGI DALAM PENDIDIKAN ISLAM - Nur Asyiah (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2013)
Conservatism is looking at everything from a religious perspective. In talking about science and education, it tends to flow purely normative and religious. Because of interpreting the reality of the universe stems from religious teachings, then all that concerns about learning, sharing of knowledge, ethics teachers and students and other educational component must originate from the religion teaching. The purpose of religion is the purpose of learning. This course is also to narrow the science space as saying that the science that must be learned only science-oriented and beneficial to the afterlife. Rational Religious flow was represented by a group of Ikhwan al-Safa. According to the Ikhwan al-Safa, the purpose of seeking knowledge is to know themselves, but the ultimate goal. As a philosophy of education, progressivism is evolved from the philosophy of pragmatism Charles S. Pierce, William James and John Dewey. But it is more important than John dewey. Dewey regarded as adherents of instrumental or eksperimental. Dewey firmly believe that education should be pragmatic and is associated with the lives of their students. He said: "Education is life, not preparation for life".